Partisipasi Komite Sekolah di SDN Ajung 3 Jember Jawa Timur - Nisa, Khoerotun; Abidin, Zainal (Program Studi Manajemen Pendidikan Islam IAIN Bone, 2024)
This research aims to discover the school committee's involvement in fundraising activities, their participation in policy and program development, and their role in facilitating the aspirations of parents and the community at State Elementary School (SDN) Ajung 3 Jember. This study used a qualitative approach to understand the phenomenon of implementing educational quality improvement strategies through the engagement of the school committee at SDN Ajung 3 Jember. Data collection techniques included interviews, observations, and document analysis. Data analysis followed an interactive process involving reduction, presentation, and verification. The research findings indicate that the school committee's participation in fundraising enhances educational quality by providing physical, financial, and conceptual support. These funds also assist in activities that enhance school quality beyond the budget and aid in formulating and establishing the School Operational Plan and Budget (RAPBS) based on principles of transparency, accountability, and democracy. The school committee plays a role in overseeing school policy implementation for sustainability. Acting as a mediator, the committee effectively facilitates the aspirations of parents and the community, receiving input that is subsequently conveyed to the school principal and discussed in meetings involving stakeholders.